Characteristics of Electrolyte Imbalance in Patients with Chronic Kidney Disease Stage 4-5 - A K M Tariqul Hasan,; Farhana Alam,; Golam Fahad Bhuiyan,; Muhammad Muhiuddin Mazuder,; T A Manzer,; Kazi Abdullah Al Mamun,; Shariful Hasan, (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Chronic Kidney Disease (CKD) is characterized by the presence of kidney damage or an estimated glomerular filtration rate (eGFR) of less than 60 mL/min/1.73 m² and persisting these conditions for 3 months or more. In case of CKD progressive loss of kidney function occurs. The kidneys play a vital role in the regulation of electrolyte and acid-base balance. With progressive loss of kidney function, derangements in electrolytes and acid-base occur which contribute to poor patient outcomes. The objective of this study was exploring the characteristics of electrolyte imbalance in patients with chronic kidney disease stage 4-5. Materials and methods: A cross-sectional study was conducted at East West Medical College, from July to December 2023. A total of 100 respondents were included in this study where data were collected through structured interviews and medical record reviews. Results: The prevalence of CKD by the gender group where 46% were male and 54% were female. According to aged group 42% were from 51-60 years of age and 23%, 14% and 10%, 11% were from 41-50 years, 31-40 years, 21-30 years and >60 years accordingly. At the level of educational status 33% completed secondary level, 21% completed primary, 20% completed higher secondary level and 15%, 12%, and 4% completed Graduation, able to read and write and illiterate accordingly. Among all respondents 52% were employed and 48% were unemployed. According to economic status 44% belongs to low economic status, 40% from middle income and 16% from high income status. Majority 63% were overweight, 26% and 11% were from Normal weight and underweight accordingly. Family history of CKD 62% had positive family history and 38% had negative history. According to personal habit of excess salt intake 65% had this habit and 35% did not take excess salt. Among all respondents most of the patients had DM which was 51%, HTN were 42%, hypothyroidism and hyperthyroidism were 24% and 06% accordingly. The prevalence of electrolyte imbalance in patients with CKD where mild hyponatraemia were 32%, moderate and severe hyponatraemmia were 16% and 4% were accordingly. Hypernatraemia and hypokalaemia were 18% and 21%. The stages of hyperkalaemia were mild, moderate and severe and prevalence were 19%, 09% and 3% accordingly. Majority 65% were metabolic acidosis and 11% were metabolic alkalosis. Among all respondent’s hyperphosphatemia, hyperparathyroidism, hypoparathyroidism, hypocalcemia, hypercalcaemia, hypomagnesemia and hypermagnesemia deficiency were 71%, 79%, 21% 61%, 17%, 21% and 8% accordingly. Conclusion: If we maintain the screening process at early of life for case detection of CKD and established early treatment of all cases, electrolytes related complication can reduce which improve health outcome of these patients. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 26-30